2019
DOI: 10.1017/s0967199419000054
|View full text |Cite
|
Sign up to set email alerts
|

Embryo sHLA-G secretion is related to pregnancy rate

Abstract: SummaryHLA-G expression has been detected in early preimplantation embryos and it has been postulated that a relationship between embryonic expression of this factor and successful pregnancy may exist. Forty-six patients were prospectively selected from our centre ‘Unidad de Reproducción Humana, Hospital Universitario de Canarias’ for conducting this study. In all cases, metaphase II (MII) oocytes were fertilized using intracytoplasmic sperm injection 2–4 h after retrieval. Embryos were cultured individually i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…11,13 To overcome the limitation of embryo scoring system, 8,9,11,13 embryo viability molecular-biomarkers are being considered. Biomarkers, associated with positive IVF outcomes, reported thus far [18][19][20][21][22][23] include, soluble human leukocyte antigen-G: sHLA-G, [24][25][26][27][28][29][30][31][32][33][34] ubiquitin, 35 apolipoprotein-A, 36 platelet-activating factor: PAF, 37 mitochondria and its DNA content, 38,39 human haptoglobin molecule, 40,41 human chorionic gonadotrophin: hCG 42,43 and cytokines such as interleukin 1 β (IL-1β), leukemia inhibitory factor (LIF) and tumour necrosis factor α (TNF-α). 44,45 Embryo viability biomarkers are thought to be beneficial with a high predictive value for forecasting pregnancy outcome, which could act as an adjunct to embryo score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13 To overcome the limitation of embryo scoring system, 8,9,11,13 embryo viability molecular-biomarkers are being considered. Biomarkers, associated with positive IVF outcomes, reported thus far [18][19][20][21][22][23] include, soluble human leukocyte antigen-G: sHLA-G, [24][25][26][27][28][29][30][31][32][33][34] ubiquitin, 35 apolipoprotein-A, 36 platelet-activating factor: PAF, 37 mitochondria and its DNA content, 38,39 human haptoglobin molecule, 40,41 human chorionic gonadotrophin: hCG 42,43 and cytokines such as interleukin 1 β (IL-1β), leukemia inhibitory factor (LIF) and tumour necrosis factor α (TNF-α). 44,45 Embryo viability biomarkers are thought to be beneficial with a high predictive value for forecasting pregnancy outcome, which could act as an adjunct to embryo score.…”
Section: Introductionmentioning
confidence: 99%
“…33 The sHLA-G is one of the promising biomarkers considered in view of its following attributes: (1) sHLA-G expressed in pre-implantation embryos [46][47][48][49][50] and endometrium 51,52 involved in the immunoregulation of embryo development 25,26,53 and implantation, 54,55 (2) it positively correlates with embryo morphology, 30,31,55,56 IR [26][27][28]53,[57][58][59][60] and clinical pregnancy rates (CPR). 24,[27][28][29][30][31][32][33][34]53,57,59,60…”
Section: Introductionmentioning
confidence: 99%
“…In a multicenter study, it has been shown that embryo selection based on a positive sHLA‐G secretion on day‐2 could increase the odds of an ongoing pregnancy about 2.52 times 88 . In accordance, Diaz et al 89 reported significantly higher levels of sHLA‐G secretion in embryos resulted in pregnancy compared to those of unsuccessful pregnancy (28.0 ± 18.8 vs. 19.0 ± 17.6 unit/ml). More interestingly, in a meta‐analysis study conducted by Niu et al, 90 it has been revealed that embryo culture media with sHLA‐G positively associated with implantation (OR: 2.66, CI: 95%, p < .00001) and clinical pregnancy (OR: 3.79, CI: 95%, p < .00001) rates compared with those without.…”
Section: Embryo‐secreted Non‐cytokines As Markers For Embryo Selectiomentioning
confidence: 74%
“…Previous studies have revealed that higher levels of sHLA-G in an embryo culture is related to better embryo development, cleavage stages, and to a higher pregnancy rate (Kotze et al, Diaz et al, 2019). sHLA-G detection has been presented as a non-invasive method for embryo selection and a predictor of pregnancy outcome (Kotze et al, 2010;Rebmann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%